Respuesta :

Answer:

2

Step-by-step explanation:

So we are going to do

(sum of parts of the secant)(part on outside)=(sum of parts of the secant)(part on outside) .

This is what you get from doing that:

(1+x+4)(x+4)=(11+x+1)(x+1)

Simplifying:

(x+5)(x+4)=(x+12)(x+1)

We could see which value of x makes both side the same.

Choice 1: Plug in 2 for x:

(2+5)(2+4)=(2+12)(2+1)

(7    )(6    )=( 14   )(3)

      42    =  42

This equation is true.

Choice 2: Plug in 3 for x:

(3+5)(3+4)=(3+12)(3+1)

(    8)(    7)=(    15)(   4)

     56     =   60

This equation is not true.

Choice 3: Plug in 6 for x:

(6+5)(6+4)=(6+12)(6+1)

( 11   )(  10 )=( 18   )(7   )

110            =   126

This equation is not true.

Choice 4: Plug in 7 for x:

(7+5)(7+4)=(7+12)(7+1)

(12  )( 11   )=( 19   )(8)

132         =152

This equation is not true.

Answer:

The answer is A or "2"

Step-by-step explanation:

ACCESS MORE